Community Structure of Crustacean in Seagrass Ecosystem of Kecinan Beach, Pemenang, North Lombok - I Putu Bayu Putra Kastawan; Ghazali, Mursal; Candri, Dining Aidil; Setyaningrum, Tri Wahyu; Artiningrum, Novita Tri (Jurnal Biologi Tropis, 2025)
The presence of Crustacea plays an important role in the processes occurring within seagrass bed areas. One of the coastal waters that contains seagrass beds is Kecinan Beach. This beach is also frequently used by the local community for madak activities, and the high frequency of such activities poses a threat to the seagrass ecosystem and the diversity of Crustacea. Due to the lack of available data on Crustacea in the Kecinan Beach area, this study is necessary to understand the community structure of Crustacea in the seagrass ecosystem of Kecinan Beach, Pemenang District, North Lombok. Data were collected using the line transect method, with each transect measuring 50 meters in length. Along each transect, 1×1 m² quadrat plots were placed. The Crustacea community structure found in the seagrass ecosystem of Kecinan Beach, Pemenang District, North Lombok, consisted of 14 families and 31 species, with a total of 155 individuals. The diversity index at stations I, II, and III was classified as moderate. The evenness index at stations I and II was high, while the evenness index at station III was moderate. The dominance and abundance indices indicated that each station had low species dominance and low abundance.